Tyskland, Norden og sporten under Anden Verdenskrig: Den tyske sportspresses fremstilling af det tysk-nordiske sportssamarbejde 1939-1943 - Jensen, Christian Troelstrup (Forum for Idræt, 2015)
This paper concludes that the Nazi race theory in particular concerning the superiority of the “Nordic race” could be found in the German mass media when covering sport meetings (in casu the Lingiade August 1939 in Stockholm) between Germany and the Nordic countries (in this context limited to Denmark, Sweden, Finland and Norway) before the war. During the war, this changes. However present these theories were in the Nazi-rhetoric they disappear with the war also in the one example we have of a Nordic-German sports meeting in March 1941.